A randomized trial of intravenous iloprost (a stable prostacyclin analogue) versus lumbar sympathectomy in the management of Buerger's disease - Bozkurt, A. K.; Koksal, C.; Demirbas, M. Y.; Erdogan, A.; Rahman, A.; Demirkilic, U.; Sayin, A. G. (Edizioni Minerva Medica, 2006)
Aim. The aim of this study was to compare the effects of iloprost and lumbar sympathectomy (LS) in the treatment of Buerger's disease. Methods. Two hundred patients with rest pain and/or ischemic ulcers were randomized to undergo LS or 28-day intravenous treatment of iloprost. The primary endpoint was complete healing without pain or major amputation at 4 and 24 weeks. The secondary endpoints were analgesic requirement, reduction in the ulcer size, 50% reduction of the ulcer, and shift in the modified SVS/ISCVS clinical status grading scale. Results. The comparison was carried out in 162 patients (iloprost: n=84; LS: n=78). Complete healing rate was 61.9% in the iloprost group, but 41% in the LS group at the 4(th) week (P=0.012); respective values for the 24(th) week were 85.3%, 52.3%, P < 0.001. Analgesic requirement was lower in the iloprost group at the 4(th) and 24(th) weeks (P=0.0 1, and P=0.098, respectively). The size of the ulcers decreased more in the iloprost group than the LS group (P=0.044 and P=0.035 at 4(th) and 24(th) weeks); 50% reduction in the ulcer size in the iloprost group was greater than in the LS group (P=0.001 and P=0.009 at 4(th) and 24(th) weeks). SVS/ISCVS grading scale demonstrated a better clinical benefit in patients treated with iloprost (P < 0.001 at 4(th) week, and P < 0.001 and at 24(th) week). Conclusion. The results of this independent study indicate that using iloprost relieves ischernic symptoms better than LS. In the era of stable prostacyclin analogues, there is no reliable evidence to support the use of LS in Buerger's disease.
16th European Chapter Congress of the International-Union-of-Angiology -- OCT 25-27, 2005 -- Glasgow, SCOTLAND
Keywords: Buerger's disease; thromboangiitis obliterans, surgery; lumbar sympathectomy; iloprost; prostaglandins; prostacyclin analogues, and derivates